C-Src inhibitor PP2 inhibits head and neck cancer progression through regulation of the epithelial–mesenchymal transition. Issue 6 (March 2023) - Lee, SunYoung; Park, Sunjung; Ryu, Jae-Sung; Kang, Jaegu; Kim, Ikhee; Son, Sumin; Lee, Bok-Soon; Kim, Chul-Ho; Kim, Yeon Soo
Head and neck squamous cell carcinoma (HNSCC) is one of the most common cancer, causing considerable mortality and morbidity worldwide. Although HNSCC management has been extensively studied, the treatment outcomes have not improved – the 5-year survival rate of patients with HNSCC is 40%. Recent studies on the development of a novel HNSCC treatment have highlighted proto-oncogene tyrosine-protein kinase Src (c-Src) as one of the major therapeutic targets. However, the clinical efficacy of c-Src inhibitors against HNSCC was not comparable to that obtained in vitro . Furthermore, the molecular mechanisms underlying the efficacy of c-Src inhibitors remain elusive. In this study, we assessed the efficacy of 4-amino-5-(4-chlorophenyl)-7-(dimethylethyl)pyrazolo[3, 4-d] pyrimidine (PP2), a selective c-Src inhibitor on HSNCC. Nine HNSCC cell lines (SNU1041, Fraud, SNU46, SNU1076, SNU899, SCC1483, YD15, YD9, and YD10-) were screened, and the effects of PP2 were evaluated using wound healing, apoptosis, and invasion assays. Western blot analysis of downstream markers was conducted to assess the specific mechanism of action of PP2 in HNSCC. The therapeutic efficacy of PP2 was further evaluated in xenograft mice. PP2 reduced tumor cell growth both in vitro and in vivo . Furthermore, it enhanced tumor cell apoptosis in cell lines and prevented metastasis in mice. PP2 also regulated the epithelial–mesenchymal transition pathway downstream of c-Src. More specifically, in SCC1483 and YD15PP2 HNSCC cell lines, PP2 exposure downregulated Erk, Akt/Slug, and Snail but upregulated E-cadherin. These results suggest that PP2 inhibits cell growth and progression in HNSCC by regulating the epithelial–mesenchymal transition pathway.